Insulation evaluation of MV underground cable with partial discharge and dielectric dissipation factor measurements - Arikan, Oktay; Uydur, Cihat Cagdas; Kumru, Celal Fadil (ELSEVIER SCIENCE SA, 2023)
As it is known overvoltage and impulse voltage are the most common stresses that cables are exposed to in practice. Since the occurrence frequency, duration and amplitude of these two stresses are different, their deteriorating effects on the cable insulation also differ. At this point, it is necessary to know how sensitively the preferred dielectric diagnosis method can detect the deteriorations on cable insulation. Since it is not technically possible to detect all isolation errors with a single preferred diagnostic method, the methods must be used together in a certain procedure. In this study, 12/20.8 kV, XLPE insulated Cable Samples were artificially aged using 50 aging cycles of overvoltage (36 kV and 60 kV) and 50 kV, standard positive impulse voltage. After each aging cycle, dielectric performance of cable insulation was measured using partial discharge (PD) and dielectric dissipation factor (DDF) methods. The accuracy of dielectric diagnosis methods due to overvoltage and impulse voltage are analyzed and discussed based on the measurement results. In order to analyze dielectric diagnostic performances of the methods, both individual trends and the correlation between PD and DDF parameters during overvoltage and impulse voltage aging processes were shared. As a result, it was found that diagnostic perfor-mances of PD and DDF methods differ according to the amplitude and waveform of the applied electrical stress. Therefore, a dielectric diagnosis procedure for MV cables including both PD and DDF methods to improve diagnostic process in field applications was proposed. In this context, the use of the proposed diagnosis procedure will contribute to the evaluation of the findings resulting from the diagnostic methods during the operation of MV cables.
Keywords: Diagnosis procedure; Dissipation factor; Electrical stresses; Partial discharge; Operation of XLPE cable; LOW-FREQUENCY; KV XLPE; VOLTAGE; VLF; Engineering